A NEW MEGADOLODINAE (MAMMALIA, LITOPTERNA, PROTHEROTHERIIDAE) FROM THE URUMACO FORMATION (LATE MIOCENE) OF VENEZUELA - Carlini A.A.; Gelfo Ja.N.; Sanchez R. (My University, 2006)
A new genus and species of Proterotheriidae Megadolodinae, Bounodus enigmaticus, from the Upper Miocene Urumaco Formation of Venezuela, is described on the basis of a poorly preserved right maxillary fragment with brachydont cheek teeth. Teeth and alveoli preserved are interpreted as part of the alveolus of P3 and P4-M3. The new taxon differs from Megadolodus, the only other known genus of the subfamily, in having a proportionally smaller P4 and M1, the latter elongated antero-posteriorly and with the protocone root more mesial than that of the hypocone. Bounodus enigmaticus gen. et sp. nov., reinforces the hypothesis that the Megadolodinae represent a distinct radiation within the Proterotheriidae, the two other major clades being the Anisolambdinae and Proterotheriinae.
Keywords: BOUNODUS ENIGMATICUS; NATIVE UNGULATES; MIOCENE; TERTIARY; SOUTH AMERICA; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен